2015
DOI: 10.1111/jzo.12269
|View full text |Cite
|
Sign up to set email alerts
|

Habitat differences do not explain population declines of sable antelope in an African savanna

Abstract: Sable antelope, Hippotragus niger, populations have declined substantially in Kruger National Park, South Africa despite large-area protection from land use and poaching. Since Africa’s large mammal populations are restricted to protected areas, understanding how to manage parks for biological diversity is critically important to the sustainability of faunal populations into the future. To better understand the drivers of sable decline, we analyzed landscapes where herds persist in the Pretoriuskop region of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Studies on birds and invertebrates showed the greatest ecosystem variety (eight and six ecosystems, respectively; Figure 3B), while the remaining taxonomic groups were studied in five different ecosystems. This included six mammal studies in rainforest [10,21,[63][64][65][66], four studies in African savannahs [67][68][69][70], three articles of invertebrates in savannahs [28,71,72], or seven articles of birds in agroecosystems [53,[73][74][75][76][77][78]. Whereas reptile studies were conducted in the rainforest [24], agroecosystem [79], or inland and coastal waters [51], amphibian studies were restricted to seasonal ponds within temperate forests (N = 3).…”
Section: Geographic Distribution Taxonomic Groups and Ecosystems Surveyedmentioning
confidence: 99%
“…Studies on birds and invertebrates showed the greatest ecosystem variety (eight and six ecosystems, respectively; Figure 3B), while the remaining taxonomic groups were studied in five different ecosystems. This included six mammal studies in rainforest [10,21,[63][64][65][66], four studies in African savannahs [67][68][69][70], three articles of invertebrates in savannahs [28,71,72], or seven articles of birds in agroecosystems [53,[73][74][75][76][77][78]. Whereas reptile studies were conducted in the rainforest [24], agroecosystem [79], or inland and coastal waters [51], amphibian studies were restricted to seasonal ponds within temperate forests (N = 3).…”
Section: Geographic Distribution Taxonomic Groups and Ecosystems Surveyedmentioning
confidence: 99%
“…Metrics of landscape‐level forage quantity for browsers and grazers were derived using remotely‐sensed vegetation cover. For browse quantity, we first measured woody vegetation volume at herbivore‐specific heights (Table 1) across the landscape following Asner et al (2015). We computed a metric of vegetation density from the LiDAR data by first binning and counting the LiDAR returns in a three‐dimensional grid with a step size of 5 × 5 × 0.5 m (defined as voxels), where the first two dimensions of the grid are east and north coordinates and the third is height above ground.…”
Section: Methodsmentioning
confidence: 99%
“…They need to be related to habitat features. For example, places no longer supporting sable antelope herds showed no differences in tree cover as revealed by LiDAR imagery from areas within occupied home ranges (Asner et al ), suggesting that features of the grass cover may be more influential. Conditions leading animals to wander beyond their usual home ranges need to be identified, because opportunities for wider space use may be critical for survival during extreme conditions.…”
Section: How Do Herbivore Species Use Space Within Home Ranges?mentioning
confidence: 99%